The etymology of the toponyms Thagaste (Numidia) and Tegueste, Tagaste, Igueste, Teguisse (Canary Islands): tracing back from Proto-Amazigh to Paleo-Amazigh (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
Thanks to the maturity reached by Amazigh historical linguistics in recent years, it is no longer reckless to undertake the complex analysis of ancient testimonies of the language—especially toponymy, ethnonymy, anthroponymy, and phytonymy—in highly heterogeneous literary and epigraphic sources (Latin, Greek, Libyan, and Neo-Punic). The study proposes a classification of Amazigh (Berber) dialect groups based on residual and diffusion areas, which provides the framework for an extensive linguistic reconstruction. It also re-examines the etymology of the Numidian toponym Thagaste and the Canarian Tegueste/Tagaste on the basis of solid phonological and morphological reconstructions, highlighting the broad relevance of Amazigh historical linguistics for the study of the ancient world in North Africa, the Iberian Peninsula, and the Canary Islands.
Keywords: Amazigh toponymy of North Africa and Canary Islands; Paleoamazigh; Amazigh dialectal classification; Thagaste; Tegueste; Tagaste